Tinjauan Capaian Pemenuhan Standar Tenaga Pendidik dan Tenaga Kependidikan Berdasarkan Standar Nasional Pendidikan di Kabupaten Tolitoli - Hasia Marto; Agung Rinaldy Malik; Burhan Burhan (JOEAI:Journal of Education and Instruction, 2020)
The purpose of this paper is to describe the data and information and views on the condition of the standard achievements of educators and education personnel in Tolitoli District. This research applies qualitative research approach descriptively, using survey method, respondents as many as 36 people spread in six subdistricts in Tolitoli district, sampling with Purposive Sampling technique. The results of research, standards of educators and education personnel consist of academic aspects and competencies of educators and education personnel. The results of the questionnaire by 36 respondents consisting of high school education level obtained an average score of 3.5 from the ideal score of 4, achievement of 86.4% categorized very well. At junior high school level obtained an average score of 2.9 from the ideal score of 4, achievement of 71.3%% is categorized quite well. At elementary school level obtained an average score of 29 from an ideal score of 4, achievement of 73.7% is categorized quite well. In conclusion, overall, each level of education meets the achievement of the standards of educators and education personnel in accordance with the national standards of education with a fairly good category. Keywords: Achievement of National Standards, Educators and Education